Cassava pest and disease surveillance data for mainland SE Asia – 2014 - Wyckhuys, Kris A.G. (International Center for Tropical Agriculture, 2016)
Results from a region-wide monitoring effort in the 2014 dry season, covering 429 fields across five countries. We present geographic distribution and field-level incidence of the most prominent pest and disease invaders, introduce readily-available management options and research needs.